Longitudinal predictors of informal and formal caregiving time in community-dwelling dementia patients - Hajek, André; Weyerer, Siegfried (Social psychiatry and psychiatric epidemiology, 2016)
Purpose: Care provided in the community for dementia patients on an individual basis may be very time consuming. Yet, little is known about the factors affecting caregiving time for community-dwelling dementia patients. Thus, we aimed to investigate the predictors of informal and formal caregiving time for these patients in a longitudinal approach. Method: Caregiving time for n = 126 community-dwelling dementia patients was assessed by proxy interviews in four assessments at 6-month intervals (1.5 years of longitudinal follow-up; AgeCoDe study). Measurement of informal caregiving time was based on a German adaptation of the Resource Utilization in Dementia questionnaire. Dementia severity was measured by the Clinical Dementia Rating (CDR). We used random effects models to estimate the effects of sociodemographic variables (age, gender, marital status and education), comorbidity and dementia severity on informal and formal caregiving time. Results: At the first assessment, mean age was 85.0 years (±3.2 years). The majority of patients was female (65.9 %), not married (divorced, single, widowed: 55.6 %) and had primary education (63.5 %). Furthermore, mean GDS was 4.4 (±0.8) and mean MMSE was 20.1 (±5.1). According to CDR, 43 individuals had very mild dementia, 55 individuals had mild dementia and 28 individuals had moderate/severe dementia. Moreover, mean total caregiving time was 3.4 h per day (±4.0). Thereof the main part represents informal caregiving time (2.3 h ± 3.4), whereas formal caregiving time was 1.2 h (±2.4). Dementia severity was associated with total caregiving time, mainly influenced by informal caregiving time. Age was positively associated with total caregiving time, driven by formal caregiving time, while being married was positively associated with total caregiving time, mainly affected by informal caregiving time. All need categories of informal caregiving time were strongly related to dementia severity, whereas none of the categories of formal caregiving time were related to dementia severity. Conclusions: Our findings extend previous studies that found an association between informal caregiving time and dementia severity. Moreover, our findings highlight the role of informal care for community-dwelling dementia patients in Germany. Informal caregiving time strongly increases with dementia severity. Consequently, as the number of patients suffering from dementia is expected to increase considerably in the next decades, there is a paramount need to strengthen the informal care system to meet patients’ needs.
Gesehen am 04.04.2019
Published online: 23 October 2015